The West Andaman Fault: A complex strain‐partitioning boundary at the seaward edge of the Aceh Basin, offshore Sumatra. Issue 5 (27th May 2014) - Martin, Kylara M.; Gulick, Sean P. S.; Austin, James A.; Berglar, Kai; Franke, Dieter; Udrekh
Abstract Along the Sumatran subduction zone, oblique strain is partitioned between the Sunda megathrust and the strike‐slip Sumatran Fault located near the volcanic arc. Additional strike‐slip motion may localize adjacent to the forearc basin system, forming the Mentawai and West Andaman Fault Zones. An alternative interpretation of the West Andaman Fault, as primarily a backthrust, has also been proposed. We combine a 2‐D multichannel seismic survey (SUMUT) acquired aboard the R/V Sonne in 2008 with previous bathymetry and seismic surveys to characterize the West Andaman Fault adjacent to the Aceh forearc Basin. Two‐dimensional Kirchoff prestack time migration of SUMUT profiles provides the clearest images to date of this portion of the West Andaman Fault. In these images we interpret inward dipping fault segments along the West Andaman Fault indicative of a transpressional flower structure. A reflector at the base of the Aceh Basin sediments (believed to be base Neogene in age) continues trenchward of the fault zone for >15 km and has geometry inconsistent with the geometry expected if a major backthrust were to daylight at the edge of the basin. Therefore, we conclude that the West Andaman Fault is predominantly strike‐slip in nature. As such, the West Andaman is likely part of a system of faults including the Sumatran Fault that accommodate the significant shear component of strain in this oblique subduction zone. Additionally, the location of the West Andaman Fault within the forearc may be controlled by the rheologic contrast between the marginal plateau and the forearc basin.